2015
DOI: 10.1002/cbic.201500249
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of a Ratiometric Fluorescent Probe Based on Arene–Metal‐Ion Contact for Endogenous Hydrogen Sulfide Detection in Living Cells

Abstract: We report the design and development of a fluorescent Cd(II) ion complex that is capable of the ratiometric detection of H2 S in living cells. This probe exploits the metal-ion-induced emission red shift resulting from direct contact between the aromatic ring of a fluorophore and a metal ion (i.e., arene-metal-ion or "AM" contact). The Cd(II) complex displays a large emission blue shift upon interaction with H2 S as the Cd(II) -free ligand is released by the formation of cadmium sulfide. Screening of potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…25 The spectroscopic analyses revealed that xanthene 1 , which lacks a C9 aromatic substituent unlike fluorescein, was susceptible to nucleophilic attack by thiol species and readily converted to a non-fluorescent adduct. Since hydropersulfides (RSSHs) are more nucleophilic than stable thiols such as GSH and H 2 S, 26 we thought that this reaction-based fluorescence quenching could be exploited for selective detection of hydropersulfides.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…25 The spectroscopic analyses revealed that xanthene 1 , which lacks a C9 aromatic substituent unlike fluorescein, was susceptible to nucleophilic attack by thiol species and readily converted to a non-fluorescent adduct. Since hydropersulfides (RSSHs) are more nucleophilic than stable thiols such as GSH and H 2 S, 26 we thought that this reaction-based fluorescence quenching could be exploited for selective detection of hydropersulfides.…”
Section: Resultsmentioning
confidence: 99%
“…The varied fluorescence response of these pyronine-type probes, depending on the substituents, would be reasonably explained by the different electron donating abilities of the cyclic amines. That is, the five-membered pyrrolidine can act as a stronger electron donating substituent than the six-membered piperidine, 25 so that the tolerance to nucleophilic attack by Na 2 S 2 is in the order of 5 > 4 > 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, ratiometric assay, in which the quantification depends on the ratio of two signals instead of absolute values, has attracted widespread attention. This double-signal ratiometric technique could effectively normalize the variation in environmental changes, such as path length, background light, and scattering, and thus offer more precise measurement in analytical application than single-signal measurement. Up until now, ratiometric detection has extensively developed in fluorescence, electrochemiluminescence (ECL) and electrochemical analysis. Among them, the ratiometric fluorescence is mainly based on the use of dual-wavelength signal ratio and the ratiometric electrochemical method is based on dual-potential signal ratio.…”
mentioning
confidence: 99%
“…27,28 However, despite the advantages that make MDA among the four typical H 2 S detection mechanisms, this mechanism has not garnered attention as a strategy for the development of ratiometric detection methods except for a little example. 29,30 This is because quenching the entire spectral range of uorescence by paramagnetic Cu 2+ induces only simple uorescence enhancement instead of ratiometric changes upon addition of H 2 S. In addition, the excessively strong interaction between thiol and Cu 2+ causes other biothiols such as Cys, Hcy, and glutathione (GSH) to interfere with the reactions and reduce the selectivity of H 2 S detection, as shown in several previous studies. 22 Thus, it is crucial to develop ratiometric uorescent probes for the detection of H 2 S using other metal ions that retain the advantages of the MDA-based mechanism and also display great selectivity of H 2 S over other biothiols.…”
Section: Introductionmentioning
confidence: 95%